Disaster management: the impact of flood disaster on small medium enterprises in Malaysia - Mohd. Taib, Zaitun; Jaharuddin, Nor Siah (Universiti Putra Malaysia Press, 2015)
Flood is the most devastating natural disaster experienced which damages to human life and deterioration of environment. Malaysia has experienced major floods in various states since 1920s, but the most destructive flood in the history of the state occur currently in Kelantan in the year of 2014 which likely to exceed more than RM1 billion losses or equal to USD 300 million (Malaysia National Security Council, 2015). Floods inflicted a huge negative impact to the economy and society, especially private properties, businesses and industries such as small medium enterprises (SMEs). Most businesses are short of financing to cover the losses incurred which lead to intention to quit among the SMEs by cease operation or to run at less capacity due to the floods. Since SMEs plays a prominent role to economics, there is a need for Qardhul Hasan financing scheme in helping those affected SMEs to rebuild their business without going through complicated process and high interest rate from microfinance institutions and banks in order to obtain a loan.